Analisis Spasial Pengaruh Restorasi terhadap Dinamika Kebakaran Lahan Gambut Kabupaten Ogan Komering Ilir di Khg Sungai Burnai – Sungai Sibumbung - Endang Pratiwi, Rini; Imanudin, Momon Sodik; Harun, M. Umar (Syntax Corporation, 2025)
Abstract Pelands play a crucial role in human life as they are significant carbon (CO2) storage systems. The El Nino phenomenon impacts peatlands by causing them to dry out and become highly to fire. For the surrounding communities, peatlands can be utilized for income-generating activities such as gardening. However, due to a lack of education and financial resources for land development, the community often resorts to burning, which they perceive as an easier and more efficient method. In reality, the consequences of forest and peatland fires are substantial, affecting social, economic, and health aspects. Restoring burned peatlands requires a long time and several efforts; restoration cannot be accomplished in just a few years. This research assesses the impact of forest and land fires. Based on data obtained using Landsat-8 imagery from 2015, 2019, and 2023, significant changes in land cover have occurred. However, forest and land fires in other land use areas, which are community lands, continue to show dynamics during each El Nino season. Integration among various stakeholders is essential to educate the community on the importance of preserving peatlands.